Ultrasound of ankle and foot in rheumatology - Amit Kumar Sahu; Prasan Deep Rath; Bharat Aggarwal (Indian Journal of Rheumatology)
Ankle and foot are frequent joints to be involved in arthritis. These joints, being superficial in nature, can be easily accessed by ultrasound. Other advantages of ultrasound are its easy availability, portability, and repeatability. Tenosynovitis, synovitis, tendinosis, bursitis, and enthesopathy are common findings in inflammatory arthritis, which can be easily evaluated by ultrasound. Follow-up and treatment response can also be evaluated with less cost to the patient. High-frequency (7–15 MHz) linear probes with availability of color and power Doppler are ideal for scanning the ankle and foot. Systematic evaluation is the primary requirement for a proper assessment. Ankle is evaluated compartment wise with specific positing for anterior, posterior, medial, and lateral compartments. Foot is evaluated according to the midtarsal joints and metatarsophalangeal and interphalangeal joints. Structured base evaluation of the compartments and joints should be done and the pathologies were noted. Thus, ultrasound of the ankle and foot is a very useful and easily available modality for identifying and distinguishing different rheumatological pathologies such as tendinitis, tenosynovitis, synovitis, bursitis, and enthesopathy of the ankle and foot.